PERSEPSI GURU KIMIA DI KALIMANTAN BARAT TERHADAP PENGGUNAAN SOCIO SCIENTIFIC ISSUES (SSI) DALAM PEMBELAJARAN KIMIA - Widad, Saninah; Rahayu*, Sri; Munzil, Munzil (Jurnal Visi Ilmu Pendidikan, 2024)
This research aims to investigate the perceptions and experiences of chemistry teachers in West Kalimantan regarding the use of socio-scientific issues (SSI) in teaching. The research design employs a survey method with a participant sample of 30 teachers.. The results show that the majority of teachers express a positive attitude toward SSI-based learning as a tool to enhance students' interest, problem-solving abilities, and the relevance of chemistry materials to current social issues. Identified challenges include limited initial understanding of SSI, students' lack of literacy, and difficulties in motivating students to engage. Teachers feel the need for the development of Higher-Order Thinking Skills (HOTS) contextualized with SSI in chemistry teaching to stimulate high-level thinking skills in students. These findings emphasize the importance of teacher training, the development of relevant teaching materials, and a student-centered approach as strategies to address challenges and enhance the effectiveness of SSI teaching in chemistry classrooms.Keywords: Chemistry teachers, socio-scientific issues, higher-order thinking skills (HOTS)AbstrakPenelitian ini bertujuan untuk meneliti persepsi dan pengalaman guru kimia di Kalimantan Barat terhadap penggunaan isu-isu sosiosains (SSI) dalam pembelajaran. Desain penelitian menggunakan metode survey dengan jumlah partisipan 30 guru. Hasil penelitian menunjukkan sebagian besar guru mengungkapkan sikap positif terhadap pembelajaran SSI sebagai alat untuk meningkatkan minat siswa, kemampuan penyelesaian masalah, dan relevansi materi kimia dengan isu-isu sosial aktual. Kendala yang diidentifikasi meliputi pemahaman awal yang terbatas tentang SSI, kurangnya literasi siswa, serta tantangan dalam memotivasi siswa untuk terlibat. Guru merasa diperlukan pengembangan soal HOTS berkonteks SSI dalam pembelajaran kimia untuk merangsang keterampilan berpikir tingkat tinggi siswa. Temuan ini menekankan pentingnya pelatihan guru, pengembangan bahan ajar yang relevan, dan pendekatan kelas berpusat pada siswa sebagai strategi untuk mengatasi kendala dan meningkatkan efektivitas pengajaran SSI di kelas kimia.  Kata Kunci: guru kimia, isu-isu sosiosains, keterampilan berpikir tingkat tinggi (HOTS)